2017
DOI: 10.1111/jbi.13013
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in the evolutionary diversity of tree communities across southern South America

Abstract: Aim To determine the principal drivers of variation in the evolutionary diversity of forest tree communities, with a focus on the temperate forests of South America.Location Forests across southern South America, extending from tropical forests in southern Brazil, to the temperate forests of southern Chile and Argentina. MethodsWe compiled a database of 742 forest tree community inventories spread over six countries and 12 biomes, or major vegetation types. In total, these inventories covered 3075 species of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…Therefore, RFs are still found on the vast Amazon domain and on the Atlantic, Pacific, and Caribbean windward coastlands-the latter three much more fragmented than original [14]. Additionally, RFs are also found as riverine seasonal forests across drylands, as well as temperate rain forests in the Southern Cone [10,29]. The scattered distribution SDF concentrates across the so-called Pleistocene Arc that surrounds the Amazon basin before stretching into Mesoamerica and the Caribbean [11,15,30].…”
Section: Neotropical Forests: a Complex Vegetation Mosaicmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, RFs are still found on the vast Amazon domain and on the Atlantic, Pacific, and Caribbean windward coastlands-the latter three much more fragmented than original [14]. Additionally, RFs are also found as riverine seasonal forests across drylands, as well as temperate rain forests in the Southern Cone [10,29]. The scattered distribution SDF concentrates across the so-called Pleistocene Arc that surrounds the Amazon basin before stretching into Mesoamerica and the Caribbean [11,15,30].…”
Section: Neotropical Forests: a Complex Vegetation Mosaicmentioning
confidence: 99%
“…In this way, many lineages, such as Aextoxicon, Citronella, Cryptocarya, Drimys, Gomortega, Laurelia, Persea, Laureliopsis, Legrandia, Nothofagus, Pitavia, and Podocarpus, have diversified outside the tropics, keeping their ancestral preference for temperate conditions. Although the southern floras are considerably poorer than their tropical counterparts, they have a higher lineage diversity, that is, they hold more diversity on broader groups, such as families, which means older diversification with higher conservatism of clades in the temperate floras [10,18]. There is also a high conservation of ancestral genetic polymorphism in SDF, which is due to factors such as their arrested dynamics (see session V), low immigration rates, and notorious discontinued distribution, whose combination results in a long persistence of SDF populations and also increasing the endemism levels [11,38].…”
Section: Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…In its most basic form, quantifying the number of lineages in assemblages could consist of counting the number of species. However, the term lineage diversity is generally applied when the units are not species, but a shallower or deeper evolutionary level, i.e., within or above the species taxonomic rank (see [5][6][7][8][9] for examples below species rank; see [10][11][12][13][14] for examples above species rank). In this paper, we focus on lineage diversity above the species rank.…”
Section: Introductionmentioning
confidence: 99%
“…Assemblage B has 4x as many lineages at 70 Ma, while Assemblage D has 4x as many lineages at 5 Ma. For this reason, researchers have suggested that the amount of PD an assemblage contains above or below that expected given its SR is a better measure of ALD [12,13]. However, if we were to follow that approach, then Assemblage C might be considered to have more ALD than Assemblage D (its ratio of PD:SR is twice that of Assemblage D), even though at all phylogenetic depths Assemblage D has the same or more lineages than Assemblage C. Clearly, more work is needed to determine which metrics derived from phylogenies may provide the best measures of ALD that integrate over evolutionary timescales.…”
Section: Introductionmentioning
confidence: 99%